2002
DOI: 10.1080/20024091064318
|View full text |Cite
|
Sign up to set email alerts
|

O-Phenylphenol and its Sodium and Potassium Salts: A Toxicological Assessment

Abstract: Ortho-phenylphenol (OPP) and its sodium (SOPP) and potassium (POPP) salts are used as fungicides and disinfectants. Due to the widespread use of especially OPP and SOPP, the potential for consumer exposure and some "critical" findings the toxicological database is quite extensive and complex. In experimental animals toxicity after single oral and dermal administration of these compounds is low. For the skin and mucous membranes, OPP has to be considered as irritating, and SOPP and POPP as corrosive. A large nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 108 publications
0
25
2
Order By: Relevance
“…Among the experimental animals tested, post-implantation loss was a common developmental effect. Published and unpublished reviews have concluded that OPP and SOPP induce developmental effects only at doses where maternal effects are observed [1,2,38]. However, our analyses indicate that fetal effects may also occur at doses where maternal toxicity is either minimal or not present (summary Table 8).…”
Section: Discussioncontrasting
confidence: 45%
“…Among the experimental animals tested, post-implantation loss was a common developmental effect. Published and unpublished reviews have concluded that OPP and SOPP induce developmental effects only at doses where maternal effects are observed [1,2,38]. However, our analyses indicate that fetal effects may also occur at doses where maternal toxicity is either minimal or not present (summary Table 8).…”
Section: Discussioncontrasting
confidence: 45%
“…Ortho-phenyl phenol (OPP) is an anti-microbial agent employed as disinfectant and fungicide in the preservation of wood, treatment of citrus and vegetables, and production of textile (Bomhard et al, 2002). Its widespread use means considerable potential for occupational and consumer exposure.…”
Section: Introductionmentioning
confidence: 99%
“…For sodium salt-induced urinary bladder carcinogenesis, changes of urinary components, with elevation of the urinary pH value and Na ion concentration, are considered essential factors for activity in male rats [25][26][27] . In fact, OPP itself does not show any modifying potential for urinary bladder carcinogenesis in rats 28,29 . It has been reported that sodium L-ascorbate and Na-OPP treated mice show elevation of urinary pH value and Na ion concentration, but no morphological changes or enhanced urinary bladder carcinogenesis 30,31 .…”
Section: Discussionmentioning
confidence: 99%